A randomised controlled study of the effect of long chain polyunsaturated fatty acid supplementation on stool hardness during formula feeding. Issue 3 (1st September 1999) - Forsyth, J S; Varma, S; Colvin, M
Abstract : BACKGROUND: The passage of hard stools is significantly more common in formula fed infants than breast fed infants and this might be the result of differences in fat absorption between breast and formula fed infants. Experimental studies indicate that long chain polyunsaturated fatty acids (LCPUFAs) might influence fat hydrolysis and absorption. AIM: To investigate the relation of LCPUFA supplementation to stool frequency and consistency during the first 4 months of life. DESIGN: Double blind, randomised, controlled study of 88 healthy infants. RESULTS: 1905 stools (858 from LCPUFA supplemented infants, 1047 non-supplemented infants) were examined. The mean (SEM) number of stools passed for each three day study period was significantly less in the LCPUFA group (5.5 (0.3) v 6.2 (0.2); p < 0.05). In both groups, there was a significant reduction in the number of stools passed with age (p < 0.001). During the first 3 months, the mean (SEM) percentage of hard stools passed by infants in the LCPUFA supplemented group was 7.7 (2.1) compared with 19.2 (2.8) for unsupplemented infants (p = 0.001). CONCLUSION: The prevalence of hard stools is significantly reduced in infants fed a formula that is supplemented with LCPUFAs.